Sexual Dysfunction in Married Women With Urinary Incontinence - Zincir, Handan; Demir, Gokce; Günayd?n, Yurdagül; Ozen, Betül (Urology Journal, 2018)
Purpose: This study was conducted in descriptive and cross-sectional design in order to determine prevalence of urinary incontinence severity in women with urinary incontinence (UI), correlation between UI and sexual dysfunction Materials and Methods: The study had descriptive and cross-sectional design. In sample selection, four Family Health Centers areas were determined by lot and totally 384 women with UI were reached by making home visits in these regions. As data collection tool, severity index in female urinary incontinence determining UI condition and Female Sexual Function index determining sexual functioning were used. Results: Average age of the women participating in the study was 37.3 ± 1.02. Mean body mass index of the women was 26.3 ± 5.41. It was determined that 22.1% of the women participating in the study had UI for 3-5 years and 15.1% had UI for six years and a longer time. It was determined that 53.9% of the women participating in study had mild incontinence, 40.6% had moderate incontinence, 3.6% had severe incontinence, and 1.8% had very severe incontinence. A significant correlation was found between severity index in female urinary incontinence (ISI) score and Female Sexual Function Index (FSFI) score (p < 0.05). There was a positive and weak correlation between ISI scores and age, duration of marriage, and number of pregnancy of the women who participating in the study; and a positive and very weak correlation between ISI scores and body mass index and spontaneous abortion (p < 0.05). Conclusion: Almost half of women with UI were determined to have moderate and more severe urinary incontinence. A significant correlation was found between ISI and FSFI score.